2012
DOI: 10.1016/j.ces.2011.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Water uptake and salt transport through Nafion cation-exchange membranes with different thicknesses

Abstract: The water uptake of different aqueous salt solutions in different Nafion membranes, and the salt transport through those membranes under the driving force of a concentration gradient, have been studied. These experiments have been performed by using the following salts: lithium chloride, sodium chloride, potassium chloride and cesium chloride. Different homogeneous Nafion membranes, NF111, NF112, NF115 and NF117, have been used in this work, with the aim of studying the membrane thickness influence. It has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 39 publications
2
43
0
Order By: Relevance
“…Indeed, for moderate ly and highly cross-linked ion-exchanger s, swelling increases with the counter-ion hydration whereas this order may be partially or completely reversed in very highly cross-link ed ion-exch angers due to incomplete solvation. Various experime ntal methods were proposed and used to characterize ion-exchange membran e swelling such as the determination of the water content which is considered to be a key parameter in the transport behavior [21,22]. Indeed, the water content can be used to characteri ze the hydration state of the membran e and to give an image of possible structural modifications of it.…”
Section: Influence Of the Membrane Soakingmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, for moderate ly and highly cross-linked ion-exchanger s, swelling increases with the counter-ion hydration whereas this order may be partially or completely reversed in very highly cross-link ed ion-exch angers due to incomplete solvation. Various experime ntal methods were proposed and used to characterize ion-exchange membran e swelling such as the determination of the water content which is considered to be a key parameter in the transport behavior [21,22]. Indeed, the water content can be used to characteri ze the hydration state of the membran e and to give an image of possible structural modifications of it.…”
Section: Influence Of the Membrane Soakingmentioning
confidence: 99%
“…The influence of the nature of the counter-ion on the water content has been mainly investigated with Nafion cation-exchange membranes for which the water content values range between 4 and 30% according to the nature of the counter-ion. It was reported that the water content increases for decreasing atomic number or size of the cation and that the water content rises for increasing hydration number of the counter-ion [22][23][24][25]. In the case of alkali ions, the water content increases according to the following sequence: Cs + < K + < Na + < Li + .…”
Section: Influence Of the Membrane Soakingmentioning
confidence: 99%
“…Water transport through ion-exchange membranes has been addressed in the literature both experimentally [3][4][5] and theoretically [6][7][8]. Four mechanisms are often considered to cause water transport: I.…”
Section: Introductionmentioning
confidence: 99%
“…Membrane's water uptake is a key factor, since water is necessary to grant a good proton conductivity. 1,39,40 However, a high water uptake like that measured for the thinnest membrane can lead to a high methanol crossover, poor mechanical stability (especially at high temperature) and a possible flooding of the cell with detrimental effect on the performances. Figure 4A shows polarization and power density curves recorded with a membrane reticulated for 30 minutes at different operating temperatures (ie, 30, 50, and 70 C), while in Figure 4B, a comparison between polarization and power density curves recorded by using a thin membrane (ie, reticulation time 30 seconds) and a thick membrane (ie, reticulation time 30 minutes) is reported.…”
Section: Membrane Liquid Uptakementioning
confidence: 99%